Transferrable polymeric carbon nitride/nitrogen-doped graphene films for solid state optoelectronics. (November 2018) - Gan, Xin; Lv, Ruitao; Zhang, Tianyi; Zhang, Fu; Terrones, Mauricio; Kang, Feiyu
Abstract: Polymeric carbon nitride (PCN) is a stable semiconducting material with an intermediate band gap (2–3 eV), which is efficient for catalysis and optoelectronics. However, it is still a big challenge to synthesize large-area and transferrable PCN films for applications in solid state optoelectronics. In this work, by using nitrogen-doped graphene (NG) as a van der Waals epitaxial substrate, centimeter-size PCN films are synthesized via polymerization of melamine molecules. As-grown PCN/NG films can be then transferred onto other substrates (e.g. SiO2 /Si wafers, quartz slides, polymer substrates). Structural characterization reveals a polymerized structure of PCN films with nitrogen-containing heterocycles. By stacking PCN/NG films with graphene films, it is possible to construct a photodetector responsive to near-UV and UV illumination under ambient conditions. The responsivities of the photodetector are 0.59 mA/W and ∼30 μA/W towards 365 nm lamp and 488 nm laser, respectively. Our PCN photodetectors also show fast response times (e.g. ∼0.29 s to 488 nm laser illumination). Furthermore, our PCN photodetector can be fabricated on polymer substrates. As-obtained flexible photodetectors can maintain its photo-response after 100 times bending. Our results clearly demonstrate the possibility of employing large-area carbon-based semiconductors to meet the increasing demands of wearable and portable electronics. Graphical abstract: Image 1